2023
DOI: 10.1029/2023ja031637
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐Synchronous Tides in Mars Thermosphere CO2, Ar, and N2 Densities From MAVEN

Abstract: Measurements of CO2, Ar and N2 densities from the Neutral Gas and Ion Mass Spectrometer on the Mars Atmosphere and Volatile Evolution Mission (MAVEN) between 150 and 200 km altitude during 2015–2022 are analyzed to reveal diurnal (DW1), semidiurnal (SW2) and terdiurnal (TW3) solar‐synchronous tides in Mars thermosphere. Multi‐year‐mean tidal perturbations on a diurnal‐ and zonal‐mean background, corrected for solar flux variations, are reported as a function of latitude (48°S–48°N), altitude and solar longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…In Figure 7 we present daily averages of (a) SW electron density, (b) SW electron temperature, (c) [CO 2 ] disturbance strength, and (d) ][O2+ $\left[{{\mathrm{O}}_{2}}^{+}\right]$ disturbance strength. The quasi‐5‐month oscillations seen in Figure 7c (magenta curve) and Figure 7d (black curve) seem to reflect the time needed for MAVEN/NGIMS data to cover all the LT sectors (e.g., Forbes et al., 2023, Figure 1b; Yigit et al., 2021, Figure 2d). That is to say, the oscillations represent orbit precession effects that are unrelated to real climatological variations at Mars.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In Figure 7 we present daily averages of (a) SW electron density, (b) SW electron temperature, (c) [CO 2 ] disturbance strength, and (d) ][O2+ $\left[{{\mathrm{O}}_{2}}^{+}\right]$ disturbance strength. The quasi‐5‐month oscillations seen in Figure 7c (magenta curve) and Figure 7d (black curve) seem to reflect the time needed for MAVEN/NGIMS data to cover all the LT sectors (e.g., Forbes et al., 2023, Figure 1b; Yigit et al., 2021, Figure 2d). That is to say, the oscillations represent orbit precession effects that are unrelated to real climatological variations at Mars.…”
Section: Discussionmentioning
confidence: 90%
“…Also, Forbes et al. (2023) recently used such 120°‐Ls bins for their analyses of Martian thermospheric tides.…”
Section: Spacecraft Data Products and Processing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, any biases in the density data are minimized when cast in percent residuals from the zonal mean. Previous studies (e.g., England et al, 2016England et al, , 2017England et al, , 2019Forbes, Zhang, Fang, et al, 2023;Liu et al, 2017) demonstrated NGIMS densities to be well-suited to characterize the globalscale longitudinal variability of interest which ranges between about 5% and 50%.…”
Section: Maven/ngims Co 2 Densitymentioning
confidence: 99%
“…Mars' thermosphere (ca. 100–200 km) is strongly coupled with the lower atmosphere below via gravity waves (GWs), planetary waves (PWs), solar tides, ultra‐fast Kelvin waves (UFKWs), and with the exosphere above via solar radiation and solar wind particles (e.g., Bougher, 1995; Bougher, Brain, et al., 2017; Bougher, Roeten, et al., 2017; Bougher et al., 1999, 2000, 2009, 2015; Forbes & Hagan, 2000; Forbes, Zhang, et al., 2020, 2023; Forbes et al., 2008; Hughes et al., 2022; Gasperini et al., 2023). It is now well established that atmospheric waves propagating from the lower and middle (below ∼100 km) atmospheric regions are a leading source of longitudinal and day‐to‐day variability of Mars' thermosphere (e.g., England et al., 2016, 2017, 2019; Kumar et al., 2022; Yiğit, 2023).…”
Section: Introductionmentioning
confidence: 99%